School health performance score: a comparative study between rural and urban school performance - Chavan, Vishwajeet Manohar; Chavan, Girish Manohar (International Journal Of Community Medicine And Public Health, 2018)
Background: Safe, secure and healthy environment for children to learn better and face the challenges of future life can be achieved by school sanitation and hygiene education. The objective of the study was to study School health performance score and compare between rural and urban school performance. Methods: A cross sectional study was carried out. It included randomly selected 46 rural schools and 11 urban schools. Both the school was compared in terms of school health services parameters. Results: In our study, 33854 students in total were enrolled from 46 rural schools as compared 9904 students from 11 urban schools. Mean number of students per school was noted to be 735.95±303.72 in rural schools and 900.36±172.83 students in urban schools. From the 46 rural school teachers, 7 teachers had semi-English as their mode of teaching as compared to 39 teachers whose mode of teaching was Marathi; while all the 11 urban school teachers taught their students only in Marathi. Conclusions: It was found that the school performance score overall as well as on individual item studies was significantly better in urban schools than the rural schools.